(untitled) (Al-Academy, 2022)
This research aims to determine the Attitudes Towards Fashion accessories of Saudi youth, and the descriptive analytical method was used in this research. The research sample was 500 youth in Riyadh that age between 20 to less than 40. The most important results show that young people prefer shoes by 53.2%, that 45.2% of young people prefer acquiring modern designs in fashion accessories, and the research emphasized the importance of studying the impact of rapid economic, social and cultural developments on young people’s attitudes towards fashion and its accessories, directing the attention of Saudi fashion designers towards complements Fashion to offer designs that match their trends